1990
DOI: 10.1093/infdis/161.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to p40tax Protein of Human T Cell Leukemia Virus 1 and Infectivity

Abstract: To investigate the physiologic significance of antibody to human T cell leukemia virus type 1 (HTLV-1) tax gene product (p40tax), 147 male and 243 female HTLV-1 carriers were examined for anti-p40tax, and 104 carriers were checked for anti-p40tax an average of 5.4 times during an 8-year period. Prevalence of anti-p40tax was significantly higher in female (62.6%) than in male subjects (51.0%; P less than .05). Anti-p40tax status did not change in most during the observation period. There were significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…A similar tendency was seen in the study of the Yaeyama District of Okinawa among individuals aged over 2 years. (Kashiwagi et al, 1990). These findings support the hypothesis that anti-Tax antibody is a risk factor for HTLV-I transmission from mother to child.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…A similar tendency was seen in the study of the Yaeyama District of Okinawa among individuals aged over 2 years. (Kashiwagi et al, 1990). These findings support the hypothesis that anti-Tax antibody is a risk factor for HTLV-I transmission from mother to child.…”
supporting
confidence: 80%
“…Furthermore, by crosssectional analysis, the sero-prevalence of HTLV-I antibody among wives was found to be closely associated with the anti-Tax sero-status of HTLV-I carriers husbands Stuver et al, 1993). In a study of the Yaeyama Districts of Okinawa, Japan, Kashiwagi et al (1990) reported no significant difference in sero-prevalence of HTLV-I among wives according to husbands' anti-Tax sero-status. However, in the younger population (aged 30 years or less), they reported that sero-prevalence of HTLV-I was higher among wives with anti-Tax ϩ spouses than those with anti-Tax Ϫ husbands although not significantly so.…”
mentioning
confidence: 95%
“…Moreover, healthy carriers of HTLV-1 as well as patients with HTLV-1-associated diseases may lose some proviral sequences while they retain others. In such instances, it is not unusual for the tax sequence to be retained (12). Because of the low prevalence of HTLV infection in the United States, this issue has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…This transmission is linked to the presence of HTL V -1 provirus in mononuc1ear ceIls in breast milk (Kinoshita et al, , 1985a. MaternaI factors associated with transmission, which correIate with high HTL v-1 viral Ioad, are: high HTL V -1 antibody titres directed against the whole virus, presence of anti-Tax antibodies and in-vitro maternaI HTLV-I antigen expression in short-term culture (Sugiyama et aL., 1986;Hino et aL., 1987 a;Sawada et al, 1989;Kashiwagi et aL., 1990;Wiktor et al, 1993). Other factors inc1ude the presence of antibodies directed against certain immunogenic epitopes of the gp46 envelope glycoprotein and maternaI age:: 30 years (Wiktor et al, 1993).…”
Section: Serological Detection Of Specifie Antibodiesmentioning
confidence: 99%